2008
DOI: 10.4103/0970-1591.42632
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary rhinosporidiosis

Abstract: Rhinosporidiosis is a chronic granulomatous condition commonly affecting the anterior nares and nasopharynx. Apart from these two sites, infection in other sites is very rare. Here is a review of rhinosporidiosis in genitourinary organs with addition of five new cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…At pH values >7.4 its CMC was relatively low at 3.2 µg/mL as compared with other polymeric amphiphiles (5~1,000 µg/mL) 40,41 or low molecular weight surfactants (e.g., sodium dodecyl sulfate; 2.0 mg/mL). 42 Low CMC values are important for micelle stability in drug delivery applications, since sudden dilution on injection destabilizes drug loaded micelle at concentrations below their CMC. In addition, this low CMC value indicates that deprotonation of the imidazole groups of P(Asp-g-Im)-PEG at more than physiological pH values could provide more hydrophobic properties than its charged carboxyl groups due to static interaction and a greater imidazole content.…”
Section: Resultsmentioning
confidence: 99%
“…At pH values >7.4 its CMC was relatively low at 3.2 µg/mL as compared with other polymeric amphiphiles (5~1,000 µg/mL) 40,41 or low molecular weight surfactants (e.g., sodium dodecyl sulfate; 2.0 mg/mL). 42 Low CMC values are important for micelle stability in drug delivery applications, since sudden dilution on injection destabilizes drug loaded micelle at concentrations below their CMC. In addition, this low CMC value indicates that deprotonation of the imidazole groups of P(Asp-g-Im)-PEG at more than physiological pH values could provide more hydrophobic properties than its charged carboxyl groups due to static interaction and a greater imidazole content.…”
Section: Resultsmentioning
confidence: 99%
“…The excess energies of activation for viscous flow were obtained with the expression: 2 OH + x 2 C 4 H 9 NH 2 , (s); + x 2 (C 4 H 9 ) 2 NH, (n); + x 2 (C 4 H 9 ) 3 N, (h) at a temperature of 298.15 K. The solid curves have been drawn from equation (10).…”
Section: Resultsmentioning
confidence: 99%
“…Primary to tri-butylamine are moderately polar substances and are weakly self-associated, while alkoxypropanols are polar compounds. In recent years, we have been actively engaged in a systematic study involving binary mixtures of alkoxypropanols with organic solvents [1][2][3][4][5], especially in terms of evaluation of various thermodynamic properties and functions that give a better understanding of the molecular interactions. In a previous paper [6], we have reported excess molar volume V E and speed of sound u for binary mixtures of dipropylene glycol monomethyl ether with mono-, di-, and tri-alkylamines.…”
Section: Introductionmentioning
confidence: 99%
“…Ethers and 1-alkanols are also used in the chemical industry as a solvent for oils and petrol and are used in gasoline formulation as enhancement of octane rating or fuel additives. Investigations into the literature have shown that excess properties of binary mixtures containing ethers have previously been studied by several authors (Pal et al [2][3][4][5][6][7], Tovar et al [8], and Cobos et al [9]). We report in this paper the measurements on density q, speed of sound u, and viscosity g of binary mixtures containing CH 3 (OCH 2 CH 2 ) 2 OH with CH 3 (CH 2 ) 5 OH, CH 3 (CH 2 ) 7 OH, and CH 3 (CH 2 ) 9 OH at T = (293.…”
Section: Introductionmentioning
confidence: 99%